Udział braci zakonnych w nauczycielskim zadaniu Kościoła - Domaszk, Arkadiusz (Prawo Kanoniczne, 2007)
The article analyses the active part and assignments of consecrate brothers in the teaching function of the Church. The problem is examined with reference to the third book of the Code of Canon Law 1983. The author considers assignments of consecrate brothers in the ministry of the divine word, the missionary action of the Church, the Catholic education and instruments of social communication. Consecrate brothers can fundamentally participate in all teaching functions. Small limitations e. g. the prohibition of the predication of the homily during the Holy Mass are derived from theological or legal reasons.